2022
DOI: 10.2106/jbjs.cc.22.00287
|View full text |Cite
|
Sign up to set email alerts
|

Tularemia Proximal Interphalangeal Joint Septic Arthritis

Abstract: Case: A case of Francisella tularensis finger proximal interphalangeal joint septic arthritis secondary to feral cat bite is presented. The patient underwent operative debridement on presentation. On postoperative day 5, a gram-negative rod resembling F. tularensis was identified. The patient received 4 weeks of gentamicin for culture-confirmed ulceroglandular tularemia. At the final follow-up, the infection had resolved, and full function of the digit had been regained. Conclusion:Francisella tularensis septi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“… Clary et al (2022) reported a finger interphalangeal joint arthritis caused by Francisella tularensis inoculated through a cat bite. The patient was cured after receiving gentamicin for 4 weeks.…”
Section: Tularemia Treatment In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“… Clary et al (2022) reported a finger interphalangeal joint arthritis caused by Francisella tularensis inoculated through a cat bite. The patient was cured after receiving gentamicin for 4 weeks.…”
Section: Tularemia Treatment In Humansmentioning
confidence: 99%
“…F. tularensis was isolated from the aortic and periaortic tissues. He was cured after replacing the aortic graft and gentamicin plus ciprofloxacin treatment for 2 weeks then ciprofloxacin for 10 weeks 6.4.5 Prosthetic joint infections Clary et al (2022) reported a finger interphalangeal joint arthritis caused by Francisella tularensis inoculated through a cat bite. The patient was cured after receiving gentamicin for 4 weeks.…”
Section: Endocarditis and Aortic Infectionsmentioning
confidence: 99%